Optimization of manganese reduction in biotreated POME onto 3A molecular sieve and clinoptilolite zeolites - Jami, Mohammed Saedi; Rosli, Nurul-Shafiqah; Mutiu, Amosa (Water Environment Federation, 2016)
Availability of quality-certified water is pertinent to the production of food and pharmaceutical products. Adverse effects of manganese content of water on the corrosion of vessels and reactors necessitate that process water is scrutinized for allowable concentration levels before being applied in the production processes. In this research, optimization of the adsorption process conditions germane to the removal of manganese from biotreated palm oil mill effluent (BPOME) using zeolite 3A subsequent to a comparative adsorption with clinoptilolite was studied. A face-centered central composite design (FCCCD) of the response surface methodology (RSM) was adopted for the study. Analysis of variance (ANOVA) for response surface quadratic model revealed that the model was significant with dosage and agitation speed connoting the main significant process factors for the optimization. R2 of 0.9478 yielded by the model was in agreement with predicted R2. Langmuir and pseudo-second-order suggest the adsorption mechanism involved monolayer adsorption and cation exchanging. Water Environ. Res., 87 (2015).